Genetic Diversity and Population Structure of the Antarctic Toothfish, Dissostichus mawsoni, Using Mitochondrial and Microsatellite DNA Markers - Choi, Hee-kyu; Jang, Ji Eun; Byeon, Seo Yeon; Kim, Yu Rim; Maschette, Dale; Chung, Sangdeok; Choi, Seok-Gwan; Kim, Hyun-Woo; Lee, Hyuk Je (Frontiers in Marine Science, 2021)
The Antarctic toothfish, Dissostichus mawsoni, serves as a valuable fishery resource around the Antarctic Continent since 1997, managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Although delineating genetic or stock structure of populations is crucial for improving fishery management of this species, its number of genetic populations and genetic diversity levels remain ambiguous. In the present study, we assessed the population genetic and phylogeographic structure of the Antarctic toothfish across 20 geographic localities spanning from Subareas 88 (88.1, 88.2, and 88.3) to Subareas 58 (58.4 and 58.5) by using mitochondrial DNA (mtDNA) cytochrome oxidase I (COI) and 16S rRNA (16S) sequences and seven nuclear microsatellite loci. MtDNA revealed a low level of polymorphism (h = 0.571, π = 0.0006) with 40 haplotypes in 392 individuals, connected only by 1–5 mutational steps, which is indicative of shallow evolutionary history. Microsatellites showed a range of allelic richness (AR) from 6.328 (88.3 RB3) to 7.274 (88.3 RB6) within populations. Overall genetic diversity was generally higher in Subareas 58 than in Subareas 88, suggesting that effective population size (NE) is larger in Subareas 58. The results of population analyses using microsatellites suggest that the sampled populations are likely to comprise a well-admixed single gene pool (i.e., one genetic stock), perhaps due to high contemporary gene flow occurring during the prolonged larval phase of this fish. However, given weak, but significant microsatellite differentiation found in six population-pairs, the possibility of existence of multiple genetic populations could not be completely excluded. The mtDNA AMOVA suggests a genetic break between the Subareas 88 and 58 groups (FCT = 0.011, P = 0.004). Moreover, mtDNA genetic distances (FST) between populations were proportionally greater as geographic distances increase. The patterns of isolation by distance (IBD) shown only in mtDNA, but not in microsatellites might suggest that population differentiation or divergence processes underwent faster in mtDNA than microsatellites, due to its NE being only one-quarter of nuclear DNA. Temporal stability in the genetic structure of D. mawsoni is also indicated by the results of no genetic differentiation between juveniles and adults. The findings of this study will help to design effective stock management strategies for this valuable fishery resource. We suggest that a long-term genetic monitoring is needed to understand the population structure and dynamics of toothfish in response to ongoing climate changes.